Daurisoline attenuates H2O2-induced chondrocyte autophagy by activating the PI3K/Akt/mTOR signaling pathway - Yang Zhang; Wenguang Liu; Zhonghao Liu; Yi Liu (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteoarthritis (OA) is a chronic degenerative joint disease characterized by cartilage degeneration and intra-articular inflammation. Daurisoline (DAS) is an isoquinoline alkaloid isolated from Rhizoma Menispermi, whose antitumor and anti-inflammatory pharmacological effects have been demonstrated, but the effects of DAS on OA have rarely been researched. In this study, we aimed to explore the potential role of DAS in OA and its partial mechanism. Materials and methods The cytotoxicity of H2O2 and DAS toward chondrocytes was detected by the Cell Counting Kit-8 assay. Safranin O staining was used to detect chondrocyte phenotype changes. Cell apoptosis was measured by both flow cytometry and quantitative analysis of the protein levels of the apoptosis-related factors Bax, Bcl-2 and cleaved caspase-3 by western blot. Western blotting and immunofluorescence were used to assess the expression of the autophagy-related proteins LC3, Beclin-1 and p62. In addition, key signal pathway targets and matrix-degrading indicators were measured by western blot. Results Our results indicated that H2O2 induced human chondrocyte apoptosis and activated autophagy in a dose-dependent manner. DAS treatment dose-dependently reversed the expression of apoptosis-related proteins (Bax, Bcl-2 and cleaved caspase3) and the apoptosis rate induced by H2O2. Western blot and immunofluorescence analyses showed that DAS decreased the H2O2-induced upregulation of the autophagy marker Beclin-1 and the LC3 II/LC3 I ratio and upregulated the p62 protein level. Mechanistically, DAS inhibited autophagy through the activation of the classical PI3K/AKT/mTOR signaling pathway and protected chondrocytes from apoptosis. In addition, DAS alleviated the H2O2-induced degradation of type II collagen and the high expression of matrix metalloproteinase 3 (MMP3) and MMP13. Conclusion Our research demonstrated that DAS alleviated chondrocyte autophagy caused by H2O2 through activation of the PI3K/AKT/mTOR signaling pathway and protected chondrocytes from apoptosis and matrix degradation. In conclusion, these findings suggest that DAS may serve as a promising therapeutic strategy for OA.